Endothelial extracellular vesicles promote tumour growth by tumour‐associated macrophage reprogramming. Issue 6 (3rd June 2022) - Njock, Makon‐Sébastien; O'Grady, Tina; Nivelles, Olivier; Lion, Michelle; Jacques, Sophie; Cambier, Maureen; Herkenne, Stephanie; Muller, Florian; Christian, Aurélie; Remacle, Claire; Guiot, Julien; Rahmouni, Souad; et al.
Abstract: Tumour‐derived extracellular vesicles (EVs) participate in tumour progression by deregulating various physiological processes including angiogenesis and inflammation. Here we report that EVs released by endothelial cells in a mammary tumour environment participate in the recruitment of macrophages within the tumour, leading to an immunomodulatory phenotype permissive for tumour growth. Using RNA‐Seq approaches, we identified several microRNAs (miRNAs) found in endothelial EVs sharing common targets involved in the regulation of the immune system. To further study the impact of these miRNAs in a mouse tumour model, we focused on three miRNAs that are conserved between humans and mouse, that is, miR‐142‐5p, miR‐183‐5p and miR‐222‐3p. These miRNAs are released from endothelial cells in a tumour microenvironment and are transferred via EVs to macrophages. In mouse mammary tumour models, treatment with EVs enriched in these miRNAs leads to a polarization of macrophages toward an M2‐like phenotype, which in turn promotes tumour growth.